2011
DOI: 10.2106/jbjs.i.01535
|View full text |Cite
|
Sign up to set email alerts
|

Unfocused Extracorporeal Shock Waves Induce Anabolic Effects in Rat Bone

Abstract: This study shows that a single treatment with extracorporeal shock waves induces anabolic effects in both cancellous and cortical bone, leading to improved biomechanical properties. Furthermore, treatment with extracorporeal shock waves results in transient damage to the bone marrow, which might be related to the anabolic effects. After further examination and optimization, unfocused extracorporeal shock waves might enable local treatment of skeletal sites susceptible to fracture.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

4
23
1
2

Year Published

2012
2012
2019
2019

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 33 publications
(30 citation statements)
references
References 36 publications
4
23
1
2
Order By: Relevance
“…Extracorporeal shockwave therapy may provide multiple benefits after stifle surgery by increasing comfort and use of the limb while also stimulating bone healing. 16,30,31 Overall, the study results support growing evidence that percutaneous ESWT may benefit TPLO recovery in dogs. Promotion of bone healing is a previously documented effect of ESWT.…”
Section: Discussionsupporting
confidence: 75%
“…Extracorporeal shockwave therapy may provide multiple benefits after stifle surgery by increasing comfort and use of the limb while also stimulating bone healing. 16,30,31 Overall, the study results support growing evidence that percutaneous ESWT may benefit TPLO recovery in dogs. Promotion of bone healing is a previously documented effect of ESWT.…”
Section: Discussionsupporting
confidence: 75%
“…Despite the widespread use of shockwave therapy for orthopedic procedures, the underlying mechanism of action by which shockwaves improve bone healing has remained unclear [37, 38]. Histological studies provide evidence that shockwave treatment stimulates osteogenesis, but clinical and experimental studies supporting this notion have been lacking [37–39]. In this study, we investigated whether shockwaves elicit hMSC responses that could explain the beneficial clinical findings others and we have made with shockwave therapy of nonunion long bone fractures.…”
Section: Discussionmentioning
confidence: 99%
“…So far, research into the molecular and cellular mechanisms of new bone formation and biocalcification after exposure of bone to ESWs has to the best knowledge only been conducted in vertebrate models (e.g. Bulut et al, 2006; Rompe et al, 2001; van der Jagt et al, 2011). Tischer et al (2002) demonstrated that ESWs can induce new bone formation inside and outside the focus zone.…”
Section: Discussionmentioning
confidence: 99%